PSP full helicopter Out ground effect - Silva, Paulo (Cranfield University, 2023)
This data contains results file of the PSP rotor with fuselage for out of ground effect
Keywords: CFD'; 'helicopter'; 'out ground effect'; 'PSP'; 'vortex flow'